Local perceptions on factors influencing the introduction of international healthcare accreditation in Pakistan - Sax, Sylvia; Marx, Michael (Health policy and planning, 2014)
Abstract. One contributor to poor health outcomes in developing countries is weak health systems; key to strengthening them are interventions to improve quality
Published 12 November 2013
Gesehen am 17.11.2020